Mutagenesis and Modeling To Predict Structural and Functional Characteristics of the Staphylococcus aureus MepA Multidrug Efflux Pump - Schindler, Bryan D. (American Society for Microbiology, 2013)
MepA is a multidrug and toxin extrusion (MATE) family protein and the only MATE protein encoded within the Staphylococcus aureus genome. Structural data for MATE proteins are limited to a single high-resolution example, NorM of Vibrio cholerae. Substitution mutations were created in MepA using gradient plates containing both a substrate and reserpine as an efflux pump inhibitor. Site-directed mutagenesis of plasmid-based mepA was used to reproduce these mutations, as well as unique or low-frequency mutations identified in mepA-overexpressing clinical strains, and to mutagenize conserved acidic residues. The effect of these changes on protein function was quantitated in a norA-disrupted host strain by susceptibility testing with and without inhibitors and by determining the proficiency of ethidium efflux. Up-function substitutions clustered in the carboxy half of MepA, near the cytoplasmic face of the protein. Repeated application of the same gradient plate conditions frequently reproduced identical substitution mutations, suggesting that individual residues are required for interaction with specific substrates. Acidic residues critical to protein function were identified in helices 4 and 5. In silico modeling revealed an outward-facing molecule, with helices 1, 2, 4, 7, 8, and 10 having contact with a central cavity that may represent a substrate translocation pathway. Functionally important residues within this cavity included S81, A161, M291, and A302. These data provide a critical starting point for understanding how MATE multidrug efflux proteins function and will be useful in refining crystallographic data when they are available.